PERFORMANCE OF DIFFERENT FENNEL BASED INTERCROPPING SYSTEMS UNDER VARYING NITROGEN LEVELS - KUMAR, ASHOK; SINGH, RANBIR; CHHILLAR, R.K. (Annals of Agricultural Research, 2014)
The field experiment was conducted to study the response of different fennel based cropping systems to varying levels of nitrogen during rabi season of 2000-01 and 2001-02 at Indian Agricultural Research Institute, New Delhi. The fennel + fenugreek intercropping system tended to have the highest seed yield of fennel, fennel seed equivalent of intercrops, total equivalents, net return, net return/rupee invested and uptake of nitrogen, phosphorus and potassiu by fennel. The marked response of fennel and intercrops was found up to the application of three -fourth of recommended nitrogen level in terms of productivity, net return, net return/rupee invested; and concentration and uptake of nitrogen, phosphorus and potassium by fennel.